(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Healthcare Information Management Systems (HIMS) are integral components of modern healthcare delivery, facilitating the efficient management of patient information, streamlining administrative processes, and enhancing clinical decision-making. This article provides a comprehensive overview of HIMS, including their components, functions, benefits, challenges, and future directions.